481 Improving the Quality of Pelvic Radiographs - Making A Difference One Picture at A Time. (4th May 2021) - Saleem, S; Parikh, S; Parratt, T
Abstract: Inadequate pelvic radiographs can lead to missed pathology, necessitate repeat imaging, and subsequently compromise patient safety. The audit conducted aimed to assess and improve the quality of pelvic radiographs at our Trust against local and international guidelines. Retrospective analysis of pelvic radiographs over a one-month period using PACS at Colchester General Hospital was conducted. All pelvic radiographs were assessed according to International Guidelines (EUR 16250EN). Postoperative radiographs were measured against local guidelines. The results were then presented in the departmental meeting and a re-audit was performed in June 2020. A total of 190 pelvic radiographs were collected in September 2019. From the 23 postoperative radiographs, 9 did not include distal end of prosthesis. During the re-audit in June 2020 the same number of pelvic images were collected. Data showed that only 2 out of 29 postoperative images did not include the distal end of the prosthesis. The audit demonstrated need for improvement at our Trust. This was carried out through a presentation in the departmental meeting, highlighting areas that needed improvement. The re-audited results from June 2020 have shown an improvement in the quality of pelvic radiographs and have had direct implications in clinical outcomes.